Restoring restaurant design and layout: towards safer dining out experience - Che Ishak, Farah Adibah; Kang, Sing Suan; Mohd Fikeri, Nor Amalin Sahiira; Karim, Shahrim; Mohamad, Siti Fatimah (Akademia Baru Publishing Sdn Bhd, 2024)
An explosion of COVID-19 virus has engulfed the world unsparingly and various industries were affected by this pandemic at different levels. The restaurant industry in Malaysia has faced huge obstacles in applying the COVID-19 safety guidelines while maintaining its business operations. However, these guidelines have influenced restaurants’ business and forced restaurants to modify their design and layout to comply with the SOPs. In addition, restauranteurs were found to creatively implement SOPs and take extra precautions to prevent deadly virus infection within their restaurants' environments. Hence, this study aimed to 1) Identify the impact of COVID- 19 on restaurants' design and layout and 2) Explore the implementation of safe dining features in restaurants. Semi-structured interviews were conducted among 10 owners and managers of casual dining restaurants in Johor Bahru, Malaysia. The interview sessions were recorded and transcribed, whereas the data collected were analyzed using thematic analysis. The findings of this research concluded that the impact of COVID-19 on the restaurants' design and layout were found most in the reduced number of customers, influence on restaurant design and alteration of restaurant layout. Moreover, the safe dining features implemented in restaurants were the basic SOPs practices, including wearing masks, restaurant sanitation, social distancing and making good use of heating, ventilation and air-conditioning (HVAC) systems. This research filled the study gaps by extending the impact of COVID-19 on restaurant businesses and restaurant designs and layouts. This research also helped the restaurateurs to improve their establishments and create an environment that is least susceptible to diseases. Moreover, the significant indings from this study will be able to help flatten the curve of coronavirus disease and protect the public from the infection.